2016
DOI: 10.18632/oncotarget.12816
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor agonists partially restore the production of pro-inflammatory cytokines and type I interferon in Sézary syndrome

Abstract: Sézary syndrome (SS) carries a poor prognosis, and infections represent the most frequent cause of death in SS patients. Toll-like receptors (TLRs) are a family of innate immune receptors that induce protective immune responses against infections. We sought to evaluate the ability of TLR agonists to induce inflammatory cytokine, Th2 cytokine, and type I interferon (IFN-I) production by peripheral blood mononuclear cells (PBMC) of untreated SS patients. We detected impaired IL-6, IL-10 and IL-13 secretion by PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
1
7
1
Order By: Relevance
“…Among the TLRs, the most intensively expressed was TLR2, which was possibly a consequence of bacterial infection; this is not surprising considering that sepsis is a common cause of death among SS patients. This aligns with a previous finding that some patients with SS showed up-regulation of TLR2 mRNA expression in unstimulated PBMCs [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Among the TLRs, the most intensively expressed was TLR2, which was possibly a consequence of bacterial infection; this is not surprising considering that sepsis is a common cause of death among SS patients. This aligns with a previous finding that some patients with SS showed up-regulation of TLR2 mRNA expression in unstimulated PBMCs [ 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previously, we verified that TLR ligands have the ability to restore, at least partially, the expression of a broad range of cytokines and type I/III IFN in the PBMCs from SS patients [ 41 ]. We assessed the NK effector molecules, such as degranulating CD107a, IFN-γ and TNF, induced by TLR7/8 stimulation by means of flow cytometry; PMA plus ionomycin was used as a positive control.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…A previous study from our group showed a deficient immune response in patients with SS. 10 The data suggest that double-positive CD4 + CD8 + neoplastic T-cells shows a lower cytotoxic potential compared to CD4 + CD8 – cells.…”
Section: Discussionmentioning
confidence: 91%